Exploring the impact of various typologies of human capital on firms' productivity - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose Although the impact of human capital on productivity has long been discussed in prior studies, empirical evidence for African firms remains limited. The existing few studies have focussed on one type of human capital in isolation and failed to explore the distinct role of different types of human capital on productivity. The aim of this study is to examine the extent to which various typologies of human capital - schooling, on-the-job training (OJT) and slack time -, both in isolation and as a combination, contribute to the productivity of African firms. Design/methodology/approach To this end, a cross-sectional firm-level data set from 13 African countries was used. To unravel the casual relationship, propensity score matching (PSM) and multinomial endogenous switching treatment regression (MESTR) techniques were employed. Findings Results indicate that all typologies of human capital - schooling, slack time and OJT - have a significant and positive impact on firms' productivity. The findings of the study further point out that the highest payoff, in terms of increased productivity, is achieved when various typologies of human capital are used in combination, rather than in isolation, in the production process. Practical implications The policy implications are that productivity of African firms can be improved by increasing the general level of schooling; encouraging firm-sponsored OJT; and giving employees time to develop new ideas. Originality/value The present study provides important insights into the distinct role of different types of human capital on productivity. In addition, it provides empirical evidence for a region where empirical evidence is scant.
Keywords: Human capital; Enterprise Survey; PSM; MESTR; Africa; J24; D22; D24; RESEARCH-AND-DEVELOPMENT; PANEL; PERFORMANCE; COUNTRIES; EDUCATION; WORKER; SKILLS; WAGES